IDENTIFICATION OF GEOTHERMAL RESOURCES IN THE AREA OF TANGKUBAN PARAHU VOLCANO BY USING MAGNETIC METHOD - Christofery Sihotang, Willy
The presence of petroleum is decreasing rapidly and it is also possible that its use will decrease rapidly. Therefore, alternative renewable energy sources such as geothermal are needed. The use of geothermal energy can reduce the use of petroleum or other fossil fuels by about millions of barrels per year. Indonesia is located on a volcanism path above the volcanic plate which causes its existence to have many mineral resources and geothermal resources. Indonesia has the largest geothermal potential in the world, which is around 40% of the world's reserves. This is used to obtain alternative renewable energy sources that replace petroleum. Geophysical method is the method used to conduct surveys to find geothermal potential areas and in this Final Project the method used is the magnetic method. This method is carried out by means of a field survey to obtain the value of the magnetic anomaly of a location which will later determine the rock susceptibility value of the location by modeling the subsurface of the research area. From the susceptibility value of these rocks, it will be known areas that have geothermal potential. In this final project, an analysis of the geothermal potential area around Tangkuban Parahu volcano is carried out, especially in the area of Jalan Raya Subang. The data obtained from the field is then corrected for daily variations and correction of the IGRF magnetic field which is then made a total anomaly contour map using Surfer 17 software. The total magnetic anomaly contour map image obtained has a total magnetic anomaly value varying between -2200 nT to 1400 nT. This also shows that there are different magnetic properties of rocks in each location. The magnetic anomaly value in the area is dominated by a negative magnetic anomaly which indicates the presence of diamagnetic rocks. A negative magnetic anomaly indicates the presence of subsurface rock in the area that has a hotter temperature or it can be said that there is a geothermal source. The modeling is done by making a trajectory on the magnetic anomaly contour map, precisely in the area around Jalan Raya Subang. This research was conducted in 2 geophysical modeling, namely forward modeling and inversion modeling. Forward modeling is done using Mag2DC software and inversion modeling is done using ZondGM2D software. The forward modeling is made with a depth of 100 m while the inversion modeling is made with a depth of 550 m. The results obtained from future modeling are that the rocks that make up the subsurface structure of the Subang Highway area are dominated by igneous rocks and there are diamagnetic rocks which are indicated as geothermal sources in the area. Then the results obtained from the inversion modeling, namely the rocks that make up the subsurface structure of the Subang Highway area are dominated by igneous rocks and diamagnetic rocks which are indicated as geothermal sources in the area. In addition there are also minerals as a constituent material below the surface of the area. These rocks are generally formed as a result of the Tangkuban Parahu volcano eruption which brought various materials to the foot of the mountain. Based on local geological information, the existence of the Ciater hot spring adjacent to the Jalan Raya Subang area, possibly due to heating of underground water originating from Tangkuban Parahu volcano flowing through the fault plane. Therefore, the Subang Highway area is predicted to have potential geothermal resources due to the hydrothermal alteration process.